Reflectometer probe system for continuous monitoring of water quality / Hashem Mohd Ali Al-Mattarneh, Sahol Hamid Abu Bakar and Deepak Kumar Ghodgaonkar - Mohd Ali Al-Mattarneh, Hashem; Abu Bakar, Sahol Hamid; Ghodgaonkar, Deepak Kumar (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2004)
Monitoring and assessing the quality of water in streams, reservoirs, lakes, and estuaries are critical for establishing total maximum daily loads to improve water quality. Current techniques for measuring water quality involve in situ measurements and/or the collection of water samples for subsequent laboratory analysis. While these technologies provide accurate measurements for a point in time and space, they are expensive, and do not provide either the continuous, spatial or temporal view of water quality needed for monitoring, assessing, or managing water quality. This paper investigates the effectiveness of microwave retlectometer systems for predicting the Water Quality Index for rivers reservoirs and lakes in Malaysia. Microwave retlectometer shows a potential to determine the salinity and some quality index using the measured retlection and dielectric properties. The microwave retlectometer simplifies and speeds up the computation of the Water Quality Index, as compared to the currently existing method. By optimizing the calculation, a significant saving in terms of money and time can be achieved.